Effectiveness of students mentoring in exclusive breastfeeding in the districts Aceh Besar and West Aceh - Cut Sriyanti; Nizwar Siregar; Mudatsir Mudatsir; Azhari Gani (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2019)
Breast milk was a food source to meet all the baby's needs for nutrients. Early initiation of breastfeeding may improve survival of children, improve health status, and improve brain development and motoric. Efforts to improve the health of infants with exclusive breastfeeding can be done by involving students with the mentoring process. This studied aims to find out the level of success of mentoring by students on the provision of breastfeeding exclusive in Aceh Province. The project design was cross-sectional study with a number of subjects were 86 infant under two years. The sampling technique uses cluster sampling. Data analyses using Chi-Square test. The results of the studied found that of 43 respondents who received a breastmilk income, 76,7% gave exclusive breastfeeding and 23,3% did not give exclusive breastfeeding. Then of 43 respondents who did not get the assistance, as 53,5% gave exclusive breastfeeding, and 46,5% did not give exclusive breastfeeding. Results known to have a significant relationship between mentoring with exclusive breastfeeding (p= 0,020). Students mentoring is effective in increasing the provision of exclusive breastfeeding to infant under two years of age. ASI merupakan sumber makanan untuk memenuhi semua kebutuhan nutrisi pada bayi. Inisiasi menyusui dini dapat meningkatkan kelangsungan hidup anak-anak, meningkatkan status kesehatan, dan meningkatkan perkembangan otak dan motorik. Upaya meningkatkan kesehatan bayi dengan pemberian ASI eksklusif dapat dilakukan dengan melibatkan siswa dengan proses pendampingan. Penelitian bertujuan untuk mengetahui tingkat keberhasilan pendampingan oleh siswa tentang pemberian ASI eksklusif di Provinsi Aceh. Desain penelitian adalah studi cross-sectional dengan jumlah subjek 86 anak di bawah dua tahun. Teknik pengambilan sampel menggunakan cluster sampling. Analisis data menggunakan uji Chi-Square. Hasil penelitian menujukkan bahwa dari hasil pendampingan oleh siswa terdapat 76,7% yang telah memberikan ASI eksklusif. Sedangkan tidak mendapatkan pendampingan hanya sebesar 53,5% yang memberikan ASI eksklusif. Terdapat hubungan signifikan antara pendampingan dengan pemberian ASI eksklusif (p= 0,020). Kesimpulan, pendampingan siswa efektif dalam meningkatkan pemberian ASI eksklusif untuk bayi di bawah usia dua tahun. Saran, perlu penguatan kepada dinas pendidikan bahwa lintas sektor ini sangat bagus dalam meningkatkan kesehatan masyarakat.